2013
DOI: 10.1111/bij.12194
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary directional asymmetry and shape variation inDiabrotica virgifera virgifera(Coleoptera: Chrysomelidae): an example using hind wings

Abstract: The western corn rootworm Diabrotica virgifera virgifera LeConte is a pest of maize in the USA and Europe and especially a problem in particular regions of Croatia. In the present study, patterns of variation in hind wing shape were examined. The first objective was to examine the influence of soil type on 10 populations of D. v. virgifera sampled from three regions in Croatia that differed according to edaphic factors and climate. The second objective was to investigate the potential evolutionary presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 47 publications
4
34
1
1
Order By: Relevance
“…The content of humus on both locations was similar. Higher ground beetle abundance recorded at location Lukač is opposite to statements of previous researches (Barbercheck, 1992;Benitez et al, 2014;Hong et al 2007;Turpin and Peters, 1971) who found that large proportion of sand could have a negative impact on larval survival. We can conclude that pH value and soil structure have the great influence on ground beetle abundance in our survey.…”
Section: Discussioncontrasting
confidence: 88%
“…The content of humus on both locations was similar. Higher ground beetle abundance recorded at location Lukač is opposite to statements of previous researches (Barbercheck, 1992;Benitez et al, 2014;Hong et al 2007;Turpin and Peters, 1971) who found that large proportion of sand could have a negative impact on larval survival. We can conclude that pH value and soil structure have the great influence on ground beetle abundance in our survey.…”
Section: Discussioncontrasting
confidence: 88%
“…This finding is similar to other studies of other structures particularly mouse skull [24] & humerus [25] as well as wings of several insect species coming from different families [26], [27] but first recorded in insect metasternum. The reasons for the significant right side variation in metasternum morphology in this group of populations are still yet to be elucidated.…”
Section: Shown Insupporting
confidence: 91%
“…Directional asymmetry is widely common used among animals, particularly in internal organs [32]. In contrast, external asymmetries like DA are less prevalent but might be an adaptive form of asymmetry, corresponding to optimal fitness caused by a selective pressure [26]. Further research should be done to determine whether this argument holds true for B. longgissima metasternum.…”
Section: Shown Inmentioning
confidence: 99%
“…Morphology can be studied by analyzing morphometric measurements (i.e. Studies have analyzed the effects of environmental conditions on insect morphology, obtaining important information about the effects of ecological factors using geometric morphometry (GM; Benítez et al 2014aBenítez et al , 2014bLemic et al 2016;Mikac et al 2016;Lunardi et al 2017). host and growing conditions; Rohlf & Marcus 1993;Adams & Rohlf 2000;O'Higgins 2000;Henderson 2006).…”
Section: Introductionmentioning
confidence: 99%
“…shape and size) and it's changes in relation to other factors (e.g. These studies have provided evidence of developmental instability, as well as differences between biotypes regarding environmental conditions (soil type, climate and nutrition; Lemic et al 2014;Benítez et al 2014aBenítez et al , 2014b. Studies have analyzed the effects of environmental conditions on insect morphology, obtaining important information about the effects of ecological factors using geometric morphometry (GM; Benítez et al 2014aBenítez et al , 2014bLemic et al 2016;Mikac et al 2016;Lunardi et al 2017).…”
Section: Introductionmentioning
confidence: 99%